MENGUNGKAP RAHASIA BUAH KURMA DAN ZAITUN DARI PETUNJUK HADIS DAN PENJELASAN SAINS - Soebahar, Erfan; Daenuri, Edi; Firmansyah, Arizal (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
This article reveals hadith instructions on palm fruit and olives in terms of value and quality tradition of understanding meaning, and in terms of secret scientific explanations about it. Research conducted by using a qualitative approach. Researchers in collecting the data for guidance and for an explanation of the secret traditions use the same science literature study. The data obtained in the Hadith-Takhrij very briefly, then edited and organized alongside the confidential data of science, then both analytically analyzed descriptively. The results showed that, first of hadith on a date worth marfu 'authentic and traditions of olives worth hasan Saheeh. This means that the hadith of these two types of fruit, besides having a strong argument, also has a foundation of understanding reasoning to uncover the Hadith. Secondly, from the treasury of science, described that: (1) a date nutritious anti-clotting, anti-inflammatory so it can relieve pain; can nourish the heart, blood vessels and prevent stroke; and prevent constipation, smooth bowel movement and helps the growth and health of teeth and bones, in addition to anti-oxidant, anti-bacterial and anti-fungal; (2) the olives are young can for food seasonings, and when mature oil is useful for health and beauty, because it contains flavonoid apigenin, luteolin, chryseriol and derivatives or omega-9, thus effectively increasing the antioxidant activity in plasma, and protects cells from LDL oxidation.